THE ESSENCE AND ROLE OF THE DUE DILIGENCE IN MERGERS AND ACQUISITIONS PROJECTS - P. Kukushkin (Publishing House of the State University of Management, 2018)
In modern Russian science, due diligence is not sufficiently studied part of mergers and acquisitions. Due diligence is currently little used in domestic practice due to the lack of methodological justification for this type of activity. The purpose of this work is to reveal the role and essence of due diligence. The article substantiates the necessity of its implementation within the framework of mergers and acquisitions projects, as a necessary stage, which minimizes the further financial risks for the acquirer, and considers the process of its implementation organizations within the stakeholder approach.